1.
Przekształć iloczyny na sumy :
a) 3(a-2)=
b) -4(x+y)=
c) -5(-x+1)=
d) -3a(jedna trzecia -a)=
e) (t-2s-1)*7=
f) jedna druga (2a-4b+1)=
g) m(2m+3)=
h) 3p(2r+5p-1)=
i) xy(2x-3y+5)=

2.
Przekształć ilorazy na sumy :
a) (-4x+8):4=
b) (6p do kwadratu -8pr):(-2)=
c) (x do kwadratu + x-1):(-jedna szosta)=

1

Odpowiedzi

2010-03-09T17:35:41+01:00
1.
a) 3a-6
b) -4x-4y
c) 5x-5
d) a²
e) 7t-14st-7
f) a-2b+½
g) 2m²+3m
h) 6pr+15p²-3p
i) 2x²y-3xy²+5xy

2.
a) =(-4x+8)*¼=-x+2
b) =(6p²-8pr)*(-½)=-3p²+4pr
c) =(x²+x-1)*(-6)=-6x²-6x+6
1 5 1